2012
DOI: 10.2340/00015555-1259
|View full text |Cite
|
Sign up to set email alerts
|

Phylloid Hypermelanosis in a Child with Psychomotor Delay, Cicatricial Alopecia, Hearing Loss and Polythelia

Abstract: Phylloid hypermelanosis is a rare form of pigmentary mosaicism that has been reported only a few times in the literature (1-6). While phylloid hypomelanosis is linked to trisomy 13, the cause of phylloid hypermelanosis is more obscure (5,(7)(8)(9)(10)(11)(12)(13). We describe here a case of phylloid hypermelanosis associated with mild developmental delay, cicatricial alopecia, hearing loss and polythelia. CASE REPORTThe boy was the first child of healthy unrelated Iraqi parents. He was bom at term after an une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Future research may show whether a consistent clinicogenetic entity can be found among the cases of phylloid hypermelanosis. For example, the patients described by Dockx et al and Bygum et al have some vague similarities to the present case, such as unusual facial appearance , auricular deformities , and mental deficiency , but it seems too early to postulate the existence of a distinct phenotype to be separated from the other cases of phylloid hypermelanosis. On the other hand, a nosologic relationship with phylloid hypomelanosis, reflecting mosaic trisomy 13q, is unlikely, although additional chromosome 13 material was found in one case of phylloid hypermelanosis .…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Future research may show whether a consistent clinicogenetic entity can be found among the cases of phylloid hypermelanosis. For example, the patients described by Dockx et al and Bygum et al have some vague similarities to the present case, such as unusual facial appearance , auricular deformities , and mental deficiency , but it seems too early to postulate the existence of a distinct phenotype to be separated from the other cases of phylloid hypermelanosis. On the other hand, a nosologic relationship with phylloid hypomelanosis, reflecting mosaic trisomy 13q, is unlikely, although additional chromosome 13 material was found in one case of phylloid hypermelanosis .…”
Section: Discussionmentioning
confidence: 42%
“…In a 7‐year‐old boy described by Bygum et al , phylloid hypermelanosis was associated with patchy cicatricial alopecia, polythelia, mental deficiency, hypotonia, and bilateral conductive hearing loss. Right‐sided facial hypoplasia, an extra incisor tooth on the left side of the upper jaw, and a low frontal hairline were likewise noted.…”
Section: Discussionmentioning
confidence: 98%